Differential effects of rabies and borna disease viruses on immediate-early- and late-response gene expression in brain tissues. - Fu, Z F (1993)
In situ hybridization and Northern blot analysis were used to examine expression of the immediate-early-response genes (IEGs) egr-1, junB, and c-fos, and the late response gene encoding enkephalin in the brains of rats infected intranasally with Borna disease virus (BDV) or rabies virus. In both Borna disease and rabies virus infections, a dramatic and specific induction of IEGs was detected in particular regions of the hippocampus and the cortex. Increased IEG mRNA expression overlapped with the characteristic expression patterns of BDV RNA and rabies virus RNA, although relative expression levels of viral RNA and IEG mRNA differed, particularly in the hippocampal formation. Furthermore, the temporal relationship between viral RNA synthesis and activation of IEG mRNA expression in BDV infection differed markedly from that in rabies virus infection, suggesting that IEG expression is upregulated by different mechanisms. Expression of proenkephalin (pENK) mRNA was also significantly increased in BDV infection, whereas in rabies virus infection, pENK mRNA levels and also the levels of glyceraldehyde-3-phosphate dehydrogenase mRNA were reduced at terminal stages of the disease, probably reflecting a generalized suppression of cellular protein synthesis due to massive production of rabies virus mRNA. The correlation between activated IEG mRNA expression and the strong increase in viral RNA raises the possibility that IEG products induce some phenotypic changes in neurons that render them more susceptible to viral replication.